Some common fixed point results of three self-mappings in cone metric spaces (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The aim of this paper is to present coincidence point and common fixed point results for three self mappings satisfying generalized contractive conditions.  The results presented in this paper generalize and extend several well-known results in the literature.